Decision‐making style, nicotine and caffeine use and dependence. (15th July 2015) - Phillips, James G.; Ogeil, Rowan P.
Abstract : Rationale: As therapeutic interventions are being developed utilising telehealth and mobile phones, it is important to understand how substance‐dependent individuals will respond to offers of online assistance. Objectives: The present paper considered the following: (1) how decision‐making style is associated with use and dependence upon commonly used stimulants and (2) how it influences behavioural responses to electronic offers of further information about these drugs. Method: An online survey examined patterns of nicotine and caffeine use, administered Severity of Dependence Scales for caffeine and nicotine and assessed decision‐making style using the Melbourne Decision Making Questionnaire and mood using the Kessler Distress Scale. Upon completing these scales, the 181 participants with a mean age of 28.14 years were offered further information online. Results: Stimulant dependence was associated with psychological distress. Caffeine dependence was linked to hypervigilance (panic). Decisional self‐esteem varied with stimulant dependence and Kessler Distress Scale score. Participants with high decisional self‐esteem declined electronic offers of further information. Conclusion: Confidence rather than defensive avoidance was a factor in reducing information‐seeking behaviours on the Internet. Copyright © 2015 John Wiley & Sons, Ltd.